Analysis and experimental verification of a multi-input converter for DC microgrid applications - Akar, Furkan; Tavlasoglu, Yakup; Vural, Bulent (INST ENGINEERING TECHNOLOGY-IET, 2018)
This work presents a multi-input converter (MIC) that can build a DC microgrid having renewable energy resources, balanced sources, and energy storage devices. After analysing its operation modes, a design procedure for the converter considering three different cases is provided. This procedure includes the semiconductor elements selection and design of the inductors. After this step, a detailed efficiency analysis is carried out for the studied cases. Finally, a 1kW prototype creating a photovoltaic-battery system is built. Through several experiments based on this set-up, it is shown that the theoretical analysis is accurate and the studied MIC can be successfully utilised to create DC microgrid.
Keywords: COMMERCIAL FACILITIES; ENERGY MANAGEMENT; DC/DC CONVERTER; SYSTEM; FEASIBILITY; TOPOLOGY; NETWORK; Engineering